2001
DOI: 10.1007/bf03351037
|View full text |Cite
|
Sign up to set email alerts
|

Post-prandial decrease of circulating human ghrelin levels

Abstract: Ghrelin, an endogenous ligand of the GH secretagogue-receptor, has recently been shown to stimulate GH secretion and to have orexigenic and adipogenic effects in rodents, but little is known about its regulation and biological function in humans. Gastric motor function is under control of the central nervous system; however, the afferent and efferent loops of this feedback control mechanism remain to be elucidated. In the study presented here we investigated the effect of nutrient intake on circulating human g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
366
2
27

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(415 citation statements)
references
References 9 publications
18
366
2
27
Order By: Relevance
“…[4][5][6] Reduced levels have been reported in obese subjects, 7,8 whereas increased concentrations have been found in patients with anorexia nervosa. 8,9 A preprandial rise 10 and a postprandial fall 11 in ghrelin levels indicate a physiological role of food on ghrelin secretion in humans. However, in obese subjects, food fails to suppress ghrelin levels, 12,13 or has an impaired suppressive effect compared with normal weight controls.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Reduced levels have been reported in obese subjects, 7,8 whereas increased concentrations have been found in patients with anorexia nervosa. 8,9 A preprandial rise 10 and a postprandial fall 11 in ghrelin levels indicate a physiological role of food on ghrelin secretion in humans. However, in obese subjects, food fails to suppress ghrelin levels, 12,13 or has an impaired suppressive effect compared with normal weight controls.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found marked individual variation in the changes in plasma ghrelin concentration after a standard meal, with the lowest concentration 1-4 h after the meal. Tschop et al (2001) reported that the plasma ghrelin levels were lowest 2 h after the meal, but Cummings et al (2001) reported that the lowest point was reached within 1 h after the meal. In contrast, Shiiya et al (2002) pointed out that the plasma ghrelin concentration declined to the very bottom 2 h after breakfast and 4 h after lunch and dinner.…”
Section: Discussionmentioning
confidence: 99%
“…Its level increases dramatically just before a meal and decreases within 1-4 h after the meal. However, many previous studies have examined the changes in plasma ghrelin levels after eating standardized meals with fixed calories at scheduled mealtimes (Cummings et al, 2001;Tschop et al, 2001;Shiiya et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These findings and the observations that circulating ghrelin levels are increased prior to a meal and during food deprivation and caloric restriction, as well as in disease states such as anorexia and cachexia, but reduced after a meal and in obesity (Ikezaki et al 2002;Liu et al 2008;Shiiya et al 2002;Tschop et al 2001aTschop et al , 2001bVan der Lely et al 2004;Yang et al 2007), strongly implicate ghrelin being involved in the regulatory processes controlling meal initiation, priming metabolic pathways and leading to more efficient calorie storage.…”
Section: Page 5 Of 37mentioning
confidence: 93%